Validasi multimedia fisika berbasis konstruktivis dalam pembelajaran inkuiri pada hukum newton gravitasi dan getaran harmonik sederhana untuk meningkatkan literasi sains siswa kelas X SMA - diza yuliana; HUFRI M.Si (Universitas Negeri Padang, 2019)
This research is based on the students 'low scientific literacy, multimedia used in learning has not facilitated students to improve students' scientific literacy and the learning that is done still tends to be teacher-centered. One solution to help improve students 'scientific literacy is to develop constructivist-based physics multimedia in learning inkuri to improve students' scientific literacy. The research method used is the R & D method (Research and Development) with the object of research is constructivist-based multimedia physics in inquiry learning. Based on the data analysis obtained from the two studies that have been conducted. First, constructivist-based multimedia physics designs in inquiry learning. Second, the average results of the validation analysis are 82. So, it can be concluded that constructivist-based multimedia physics in inquiry learning is stated to be very valid and can be used in X-class high school physics learning to help improve students' scientific literacy skills.